A Systematic Review and Meta-Analysis of the Presentation and Surgical Management of Patients With Carotid Body Tumours. (April 2019) - Robertson, Vaux; Poli, Federica; Hobson, Ben; Saratzis, Athanasios; Ross Naylor, A.
Abstract : Objectives: The aim was to determine the mode of presentation and 30 day procedural risks in 4418 patients with 4743 carotid body tumours (CBTs) undergoing surgical excision. Methods: This is a systematic review and meta-analysis of 104 observational studies. Results: Overall, 4418 patients with 4743 CBTs were identified. The mean age was 47 years, with the majority being female (65%). The commonest presentation was a neck mass (75%), of which 85% were painless. Dysphagia, cranial nerve injury (CNI), and headache were present in 3%, while virtually no one presented with a transient ischaemic attack (0.26%) or stroke (0.09%). The majority (97%) underwent excision, but only 21% underwent pre-operative embolisation. Overall, 27% were Shamblin I CBTs; 44% were Shamblin II; and 29% were Shamblin III. The mean 30 day mortality was 2.29% (95% CI 1.79–2.93). The mean 30 day stroke rate was 3.53% (95% CI 2.91–4.29), while the mean 30 day CNI rate was 25.4% (95% CI 24.5–31.22). The prevalence of persisting CNI at 30 days was 11.15% (95% CI 8.42–14.64). Twelve series (544 patients) correlated 30 day stroke with Shamblin status. Shamblin I CBTs were associated with a 1.89% stroke rate (95% CI 0.92–3.82), increasing to 2.71% (95% CI 1.43–5.07) for Shamblin II CBTs and 3.99% (95% CI 2.34–6.74) for Shamblin III tumours. Twenty-six series (1075 patients) correlated CNI rates with Shamblin status: 3.76% (95% CI 2.62–5.35) for Shamblin I CBTs, 14.14% (95% CI 11.94–16.68) for Shamblin II, and 17.10% (95% CI 14.82–19.65) for Shamblin III tumours. The prevalence of neck haematoma requiring re-exploration was 5.24% (95% CI 3.45–7.91). The proportion of patients with a neck haematoma requiring re-exploration was not reduced by pre-operative embolisation (5.92%; 95% CI 2.56–13.08) vs. no embolisation (5.82%; 95% CI 2.76–11.88). Pre-operative embolisation did not reduce drainage losses (639 mL vs. 653 mL). Conclusions: This is the largest meta-analysis of outcomes after CBT excision. Procedural risks associated with tumour excision were considerable, especially with Shamblin III tumours where 4% suffered a peri-operative stroke and 17% suffered a CNI.